2016
DOI: 10.1016/j.virol.2015.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Interferon but not MxB inhibits foamy retroviruses

Abstract: Foamy viruses (FV) are retroviruses that are widely distributed in primate and non-primate animal species. We tested here FV with capsids of simian and non-simian origin for sensitivity to interferon-β (IFN-β). Our data show significant inhibition of FV by IFN-β early in infection of human HOS and THP-1 but not of HEK293T cells. The post-entry restriction of FV was not mediated by the interferon-induced MxB protein that was recently identified as a capsid-interacting restriction factor targeting Human immunode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 78 publications
3
10
0
Order By: Relevance
“…In contrast to human immunodeficiency virus (HIV) and human T-cell leukemia virus (HTLV), FVs appear to be nonpathogenic in either naturally or accidentally infected hosts and maintain a lifelong infection in the host [2, 3]. Several host factors, such as Trim5α, APOBEC3G and Nmi have been studied as restrictors during PFV replication [48]. Previously, we also reported that Pirh2 inhibits PFV replication by degrading the viral trans-activator Tas via ubiquitination [9].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to human immunodeficiency virus (HIV) and human T-cell leukemia virus (HTLV), FVs appear to be nonpathogenic in either naturally or accidentally infected hosts and maintain a lifelong infection in the host [2, 3]. Several host factors, such as Trim5α, APOBEC3G and Nmi have been studied as restrictors during PFV replication [48]. Previously, we also reported that Pirh2 inhibits PFV replication by degrading the viral trans-activator Tas via ubiquitination [9].…”
Section: Resultsmentioning
confidence: 99%
“…9 c). We performed a similar experiment using a HIV-2 luciferase reporter virus [ 64 ], which is a three-plasmid lentiviral vector system that requires Vif to be co-expressed from a separate plasmid (Fig. 9 b).…”
Section: Resultsmentioning
confidence: 99%
“…All vector constructs were verified by sequencing and tested for USP18 protein expression. HIV-1 vector, pSIN.PPT.CMV.Luc.IRES.GFP (75,76), HIV-2 virus containing HIV-2 construct (pHIV-2D4), and pHIV-2 Luc SV40 (previously called pHIV-2 SEW Luc SV40) have been described before (76). The HIV-1 construct psPAX2 was obtained from the NIH, AIDS Reagent Program repository.…”
Section: Plasmidsmentioning
confidence: 99%